Determinants of Financial Distress in Non-Financial State-Owned Enterprises in Indonesia - Maura, Ikrana Shafa; Fajri, Mega Barokatul; Hakim, Adi Lukman (MEC-J (Management and Economics Journal), 2025)
The study aims to assess how liquidity, profitability, leverage, capital structure, and the audit committee influence the financial challenges faced by State-Owned Enterprises (SOEs). The research employs a purposive sampling method based on specific criteria, with 20 companies included in the study. The multiple linear correlation test reveals a strong relationship between liquidity, profitability, and company size regarding financial challenges. Analysis conducted using SPSS software indicates a significance value for the F-test, suggesting that liquidity, profitability, leverage, capital structure, and the audit committee significantly impact the financial difficulties. Furthermore, the t-test results demonstrate that liquidity, profitability, leverage, and capital structure play a role in influencing the financial challenges, whereas the audit committee does not have a significant effect.